Pengaruh Bauran Pemasaran terhadap Kepuasan Pelanggan pada Ekspor Karang Hias di PT Agung Aquatic Marine, Denpasar Bali - Rahmayati HM; Sumarni Sumarni; Al Qaidah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
One of the objectives of this study was to determine how the Marketing Mix on Customer Satisfaction on Ornamental Coral Exports at PT. Agung Aquatic Marine Denpasar Bali. The type of research used is quantitative method with data collection techniques through distributing questionnaires given to customers of PT. Agung Aquatic Marine Denpasar, Bali, the population of this study were all customers of PT. Agung Aquatic Marine Denpasar, Bali with a sample of 10 customers. the analysis technique used in this study uses simple linear regression statistical analysis with the help of the SPPS version 22 application. The results of simple regression analysis obtained the coefficient of determination with the R Square number 0.573 or 57.3%, which means that the marketing mix can contribute to customer satisfaction by 57.3 percent and the remaining 42.7 percent is influenced by variables not discussed in this study. From the partial test results, the tcount value of the marketing mix variable is 3.276> from the t table 1.859, this means that there is an influence of the marketing mix on customer satisfaction in ornamental coral exports. Thus H0 in this study is rejected and H1 is accepted, meaning that there is an Effect of Marketing Mix on Customer Satisfaction on Ornamental Coral Exports at PT. Agung Aquatic Marine Denpasar, Bali.